Uterine Fibroids: Burden and Unmet Medical Need - Al-Hendy, Ayman; Myers, Evan Robert; Stewart, Elizabeth (Seminars in Reproductive Medicine, 2017)
Uterine fibroids affect a wide cross-section of the population, with prevalence, symptom severity, and overall disease burden generally higher among black women, likely due to both genetic and environmental factors. Potential symptoms of uterine fibroids include painful and excessive uterine bleeding, interference with everyday life and self-image, and impaired fertility. Because of the high estimated prevalence and costs associated with treatments, the direct and indirect costs of uterine fibroids are substantial for both the health care system and the individual patient. Special patient populations—such as black women, women seeking to retain fertility, and women with asymptomatic fibroids—have particular treatment needs that require a variety of diagnostic methods and treatment options. Despite the widespread occurrence of uterine fibroids and newer treatment options, little high-quality data are available to formulate evidence-based guidelines that address these unmet patient needs. Specific areas in need of attention include improving diagnostic techniques, increasing patient access to early treatment, and identifying best practices for this diverse patient population.
Keywords: uterine fibroids; disease burden; economic burden; unmet medical need; leiomyomas